Correcting the algorithm for a minimum secure dominating set of proper interval graphs by Zou, Liu, Hsu and Wang - Araki, Toru; Saito, Ryuya (Discrete Applied Mathematics, 2023)
Zou et al. (2019) proposed an algorithm for calculating a minimum secure dominating set of a proper interval graph. However, we find a counterexample for which the algorithm outputs an incorrect subset of vertices. In this paper, we provide a modified algorithm and the proofs for the correctness.